Japanese collectivism: cultural heritage and gateway to the future (2019)
The current situations of the world in terms of culture and society can be analyzed within the framework of two pre-established psychological concepts: individualism and collectivism. Using the comparison of two cultures as different as Japanese and Colombian, the objective of this text is to understand, from an applied conceptual point of view, the cultural shocks that many Japanese experience when coming to Colombia and that the vast majority of Colombians live Upon arriving in the country of the rising sun.